2001
DOI: 10.1054/bjoc.2000.1588
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based cytology for primary cervical cancer screening: a multi-centre study

Abstract: SummaryThe aim of this six-centre, split-sample study was to compare ThinPrep fluid-based cytology to the conventional Papanicolaou smear. Six cytopathology laboratories and 35 gynaecologists participated. 5428 patients met the inclusion criteria (age > 18 years old, intact cervix, informed consent). Each cervical sample was used first to prepare a conventional Pap smear, then the sampling device was rinsed into a PreservCyt vial, and a ThinPrep slide was made. Screening of slide pairs was blinded (n = 5428). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
66
1
14

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 24 publications
8
66
1
14
Order By: Relevance
“…34 However, this prevalence is slightly higher than in other settings, 38 probably due in part to the high proportion (25%) of young women in our cohort; also, technical difficulties with Thinprep could have contributed to the higher rate of ASC-US and LSIL in the first and adjudicated cytology, respectively. 8 The HPV DNA assay was much more sensitive (by >25%Pt) than LBC but slightly less specific [by $5%Pt], in agreement to that reported in other trials. [11][12][13][14]38,39 AHPV, however, was much more sensitive than LBC (by >25%Pt) but had a similar specificity.…”
Section: Early Detection and Diagnosissupporting
confidence: 87%
“…34 However, this prevalence is slightly higher than in other settings, 38 probably due in part to the high proportion (25%) of young women in our cohort; also, technical difficulties with Thinprep could have contributed to the higher rate of ASC-US and LSIL in the first and adjudicated cytology, respectively. 8 The HPV DNA assay was much more sensitive (by >25%Pt) than LBC but slightly less specific [by $5%Pt], in agreement to that reported in other trials. [11][12][13][14]38,39 AHPV, however, was much more sensitive than LBC (by >25%Pt) but had a similar specificity.…”
Section: Early Detection and Diagnosissupporting
confidence: 87%
“…The use of the same cervical specimens collected for liquid-based cytology and HPV detection certainly reduces the discrepancies between the results of cytology and HPV testing for the detection of HGSIL. However, the higher sensitivity of liquid-based cytology for the detection of HGSIL observed in our study and reported in the literature 15,35 remains lower than the sensitivity of HPV testing.…”
Section: Discussioncontrasting
confidence: 69%
“…14 HC-II is a non radioactive, easy to perform, relatively rapid (5 hr of handling), liquid hybridization assay designed to detect 18 HPV types divided into high-risk (types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) and low-risk (types 6, 11, 42, 43 and 44) groups. The first studies have been particularly promising, showing a good agreement with PCR results, with a detection of HR-HPV DNA in more than 90% of high grade SIL (HGSIL).…”
mentioning
confidence: 99%
“…Nonetheless, cervical cytology has recently been rethought and set aside for its low sensitivity because frequent retesting is required after a cytologic testing report (7). In addition, controversial concerns focused on the cost-effectiveness arose when HPV testing was used as the primary means of cervical cancer screening, especially in regions with scarce resources and fragile infrastructures (8-11).Previous studies reported that liquid-based, thin-layer cytology is more accurate than conventional cervical cytology and has a potential to optimize the effectiveness of primary cervical cancer screening (12)(13)(14). Nevertheless, although the frequency of false-negative reports has decreased after using the liquid-based cytologic testing, the sensitivity of cervical cancer screening still can be improved with the development of new approaches such as DNA ploidy image cytometry based on the same specimen (15,16).…”
mentioning
confidence: 99%
“…Previous studies reported that liquid-based, thin-layer cytology is more accurate than conventional cervical cytology and has a potential to optimize the effectiveness of primary cervical cancer screening (12)(13)(14). Nevertheless, although the frequency of false-negative reports has decreased after using the liquid-based cytologic testing, the sensitivity of cervical cancer screening still can be improved with the development of new approaches such as DNA ploidy image cytometry based on the same specimen (15,16).…”
mentioning
confidence: 99%